C1q reprograms innate immune memory - Jonkman, Inge; Jacobs, Maaike M. E.; Negishi, Yutaka; van Heck, Julia I. P.; Matzaraki, Vasiliki; Martens, Joost H. A.; Baltissen, Marijke; Vermeulen, Michiel; Fayad, Zahi A.; Teunissen, Abraham J. P.; Mulder, Willem J. M.; Hilbrands, Luuk B.; et al. (Frontiers in Immunology, 2025)
Innate immune memory, also called trained immunity, is a metabolic and epigenetically regulated process that enables innate immune cells to recalibrate their inflammatory reactivity in response to pathogenic or endogenous stimuli. In addition to its function in host defense, trained immunity contributes to diverse immune-mediated diseases. We discovered that complement component 1q (C1q) is an effective modulator of innate immune memory, potently suppressing the responsiveness of myeloid cells. We found that C1q leads to profound reprogramming of myeloid cell metabolism, particularly glycolysis, and exerts control over the transcriptional regulation of important metabolic and inflammatory genes. We corroborate our findings by identifying single-nucleotide polymorphisms close to the C1q gene that are linked to induction of trained immunity by Bacillus Calmette–Guérin (BCG) or beta-glucan in healthy peripheral blood mononuclear cells. Our results reveal an immunomodulatory role for C1q and provide evidence of a molecular interaction between the complement system and innate immune memory. These findings expand our understanding of innate immune memory.